MODIFIKASI MESIN BOBOK KAYU UNTUK PENINGKATAN PRODUKTIVITAS MEBEL INDUSTRI KECIL - Karyono, Slamet; Purnomo, Edy (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The problems of the furniture industry target are about the effectiveness  of the use of wood chisel and bit machine because it hasn't fix machine bench for wood laying and the machine position that not ergonomic.  These  problems make. setting.. time longer, wood position unstable because of unfix bench, the vice easy to broken because  of  instability  of  wood,  imprecision  of  hole  position,  and  the  exhausted operator because of the machine position.The  main  goal of this  voucher  program  is to modify wood  chisel  and  bit machine for preparing the connection between pin and its hole at U.O ..TANGGUH, small scale furniture industry, so that productivity and quality  of the furniture will be improved. For mass production, every step must be done perfectly and carefully  so that every part can be connected  and constructed  correctly.  Because of the reason. above  wood  and  chisel  machine  that  strong,  easy  to  operate.: easy  to  lay  wood accurately, and ergonomic must be developed.                                   ,Wood and chisel machine that be developed has 220 cm length and 30 ernwidth of its bench so that the wood with 200 em length or 'more can be supported accurately  especially  at its parallel position to the machine vice. For operating  the machine easily, the machine bench is made approximately  50 em height, so that the operator  with  sit down  position  can operate  the  machine  without  exhausted.  The wood 'chisel and bit machine can make the hole approximately 7 em depth and 1 ern width.,   The result of the machine performance  test show that the machine  can be. operated easily without exhausted. The hole is easily to be made on wood with 200ern length without setting wood position. The hole position is automatically perpendicular  to the horizontal line of the wood so that in accordance with the hole position  on  the  wood.  There  is  no  vibration  on  bench  and  the  machine.  This condition shows that the construction design is strong enough to the vibration of the motor revolution and the hole feeding.